TRIP ASSIGNMENT MODEL WITH CONSIDERATION OF VEHICLE EMISSION: CASE FOR CIMAHI CITY - Herawati Herawati (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2011)
Many cities in Indonesia are facing problems related to traffic and transportation such as Cimahi city which is located in the west part of West Java, Bandung. Traffic growth in Cimahi is caused by industrialisation and urbanisation which represent the main factor of increasing population and travel demand in Cimahi. The Local Government of Cimahi has started to avoid congestion by improving infrastructure facilities or other traffic management. Traffic assignment in four-step modelling is carried out as a basic to simulate the traffic management system. Traffic congestion generally happens especially in peak periods caused by the increasing number of private cars. Based on the reasons, the study only considers private car as a mode of transportation that will be assigned in peak hour periods. The technique of assignment used is user equilibrium and traffic assignment is run by using generalized cost. Generalized cost is calculated by actual cost and perceived cost (emission cost). CUBE software has been employed for this research to analyze traffic performance. CUBE software applies existing condition (base) and four scenarios. After modeling scenarios, those are acquired that scenario 4 as the best alternative for congested reduction in Cimahi. Indeed, Scenario 4 is recommended because significant result of v/c ratio value reduction and reducing number of congestion links by considering emission cost.